2020
DOI: 10.1002/14651858.cd013449.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Myofunctional therapy (oropharyngeal exercises) for obstructive sleep apnoea

Abstract: Myofunctional therapy (oropharyngeal exercises) for obstructive sleep apnoea (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 73 publications
1
36
0
4
Order By: Relevance
“…In a recent meta-analysis evaluating the benefits of myofunctional therapy for the treatment of OSA, the authors concluded that myofunctional therapy may reduce daytime sleepiness and may increase sleep quality in the short term, and the certainty of the evidence ranges from moderate to very low, due to a lack of blinding, incomplete data and imprecision [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis evaluating the benefits of myofunctional therapy for the treatment of OSA, the authors concluded that myofunctional therapy may reduce daytime sleepiness and may increase sleep quality in the short term, and the certainty of the evidence ranges from moderate to very low, due to a lack of blinding, incomplete data and imprecision [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results from a meta-analysis showed that oropharyngeal exercises decrease the apnea-hypopnea index (AHI) in mild-to-moderate OSA patients when compared to sham therapy, but the certainty of the evidence is low. 7 Verma et al 8 found that 3-month oropharyngeal exercise therapy could significantly improve the minimum oxygen saturation and time duration of SaO2 < 90% of OSA patients, while the average AHI of OSA patients after training was similar to pre-treatment. Many studies indicated that progressive tongue strength training (TST) could elevate tongue strength and functional dietary intake by mouth in older individuals.…”
Section: Introductionmentioning
confidence: 98%
“…This concept of considering individual anatomy guiding treatment is also evident in a study which developed a pediatric OSA algorithm and demonstrated that tonsil size was the strongest predictor of adenotonsillectomy (AT) [ 25 ]. Myofunctional therapy (MT) is another treatment option which involves oropharyngeal exercises and has been shown to decrease AHI by 50% in adults [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%